Determinasi Faktor-Faktor yang Memengaruhi Partisipasi Anggota PKK dalam Pengembangan KUB Anggrek Desa Aska: Determinants of Factors Influencing PKK Members’ Participation in the Development of KUB Anggrek in Aska Village - Nurfadillah, Nurfadillah; Raisa, Daeva; Astaman, Putra; Megawati; Nurdin, Fadilah (Jurnal Ilmiah Manajemen Agribisnis, 2025)
This study analyzes the factors influencing the participation of PKK members in Aska Village in the development of the Orchid Smallholder Business Group (KUB Anggrek), a stagnant joint business producing banana stem crafts in Sinjai Regency. The results indicate that member participation is influenced by internal and external factors. Internal factors include motivation and self-awareness, education level, time management (limited by dual roles as housewives), and skills and experience. External factors include family support, access to information, community support and social climate, village government support, and limited market access and member mobility. These findings indicate that KUB development requires not only increasing the capacity of individual members but also creating a supportive external environment, particularly in terms of market access, institutional support, and mobility infrastructure.